Cover Feature: Synthesis of Mixed‐Functionalized Tetraacylgermanes (Chem. Eur. J. 10/2021). Issue 10 (7th December 2020) - Püschmann, Sabrina D.; Frühwirt, Philipp; Pillinger, Michael; Knöchl, Andreas; Mikusch, Marlene; Radebner, Judith; Torvisco, Ana; Fischer, Roland C.; Moszner, Norbert; Gescheidt, Georg; Haas, Michael
Abstract : Mixed functionalized tetraacylgermanes were synthesized by two innovative pathways. The entry in both strategies was provides by tetrakis(trimethylsilyl)germane. In both routes, the crucial intermediate, the germenolate, was formed, leading to the desired products. These new derivatives outperform the state‐of‐the‐art germanium‐based photoinitiators in terms of solubility and absorption properties. More information can be found in the Full Paper by M. Haas et al. on page 3338 .